One-pot synthesis of 3,4-dihydropyrimidine-2-(1H)-ones using CsF-Celite as catalyst - Sirirat Chancharunee (2018)
A facile, efficient, and environmentally benign procedure for the synthesis of 3,4-dihydropyrimidin-2-(1H)-ones via the cyclocondensation reaction of aromatic aldehyde, ethyl acetoaceate, and urea catalyzed by CsF-Celite was developed. This environmentally friendly method is superior to previous methods with respect to reaction time, yield, and workup. Copyright © Taylor & Francis Group, LLC.